Effect of environment on behaviour of additively manufactured alloys - Muhummed Farid Marican Abdullah (Nanyang Technological University, 2022)
Ti-6Al-4V is widely regarded as the workhorse alloy of the Titanium family. It has grown to become an incredibly important metal in modern manufacturing mainly due to its superior strength and corrosion resistance. One sector of modern manufacturing – Additive Manufacturing (AM) – has seen increasing interest in the exploration of AM Ti-64 for industrial and commercial use. This coincides with the demands of the Aerospace industry where geometrically complex part designs, excellent corrosion resistance, and a superior strength-to-weight ratio are highly sought after. Currently, studies on AM Ti-64 are limited to room temperature applications. This report will investigate the behaviour of AM Ti-64 at an elevated temperature (350°C), specifically its fatigue behaviour and fracture toughness, to ascertain its suitability in an Aerospace Environment.